CORRELATION BETWEEN PLAYING DIGITAL GAME AND STUDENTS ENGLISH LEARNING ACHIEVEMENT - Aprizal, M .; Salam, Uray; ., Suhartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstrak:Penelitian ini bertujuan untuk mengetahui hubungan antara memainkan permainan digital dan hasil pembelajaran bahasa Inggris siswa di kelas delapan SMP Bawari Pontianak tahun akademik 2012-2013. Penelitian ini melibatkan 35 siswa kelas delapan (VII B). Penelitian ini merupakan penelitian deskriptif. Data yang menjadi perbandingan nya yaitu berupa kuesioner dan hasil belajar siswa yang berasal dari guru yang mengajar. Kuesioner yang diberikan pada siswa terdiri dari 25 pertanyaan. Nilai hubungan antara dua variable ini di hitung dengan menggunakan rumus Person Product Moment. Adapun nilai dari analisis data tersebut adalah 0,86 yang berata memiliki korelasi yang sangat tinggi. Kemampuan bahasa yang dominan adalah kemampuan membaca. Ditemukan 11 siswa dengan kemampuan membaca di atas rata-rata nilai 70. Kata Kunci: Permainan Basis Digital, Hasil Pembelajaran Abstract:The purpose of this research is to find out the correlation between playing digital game and students English learning achievement for the eighth grade students of SMP Bawari Pontianak in Academic Year 2012 2013. This research involved 35 students of eighth grade (VIII B). This research was designed in the form of descriptive research therefore; the data of this research were obtained by administering the questionnaire and students English learning achievement score taken from the English teachers handbook. The questionnaire tested on 35 students with 25 questions. This research used Person Product Moment formula to see the correlation value. The result of analyzing data found that the correlation between playing digital game and their English learning achievement score were 0.86 which categorized by high correlation. The most dominant skill acquired is Reading skill. Based on the finding, it is found that there were 11 students got high level (above 70) deals with students response score and the rest of them are below 70. Keywords: Digital Game, Learning Achievement.